SOILS FROM CULTIVATED STANDS OF SHOREA JAVANICA - M.J. SHEEHY SKHFFINGTON (BIOTROPIA, 1987)
Soils from Shorea javanica plantations in different parts of Lampung province, South Sumatra were sampled to a depth of 50 cm and described. They varied from quite deep loamy alkaline soils near Krui, to sticky acid clays behind Ngaras. The cation content of most samples was quite high, but organic nutrients were low, suggesting volcanic origin of the soils. Preliminary observations of performance in situ of S. javanica would suggest a requirement for deep loamy, fairly alkaline soils with a moderately high exchangeable cation content for optimal yield and performance.